(untitled) (Research, Society and Development, 2022)
Gamification, a methodology based on the insertion of elements, mechanics, design and/or game narrative in other contexts, presents itself as an active methodology option capable of keeping the student motivated and engaged in their learning process. As few works about gamification assume the practical character of changing the methodological perspective from passive to active, it worries us to know how the teacher can develop a gamification strategy so that motivation and engagement favor the leading role by the students. To answer this question, this article presents the Structural Table for the Development of Gamification Strategies (STDGS) as a didactic-pedagogical resource that allows the teacher to organize and structure a methodological gamification strategy that combines game elements, motivation, engagement and models motivational learning. STDGS presents a structural plan and an organizational plan in order to establish the necessary relationships for a gamified methodological structure that does not focus only on entertainment and effectively favors the learning of students. From this perspective, we understand that it is a valuable resource for teachers who aim to develop gamification strategies, although it can be improved according to the teachers’ needs.